Implementation of Snakes and Ladders Game to Stimulate Early Childhood Numeracy Development - Nurramadani, Lilia; Ichsan, Ichsan (Southeast Asian Journal of Islamic Education, 2024)
One type of traditional game is the Snakes and Ladders game, which can significantly impact early childhood numeracy development. This research aimed to explore the implications of the Snakes and Ladders game in stimulating numeracy skills in preschool children. The type of research was descriptive qualitative with the research site at RA Al-Fattah Jangga Baru, and the subjects in this study were group B children, totaling 17 children. Data collection was done through observation, interviews, and documentation. The data analysis was conducted through data reduction, data display, and conclusion formulation. This study identified how elements of the Snakes and Ladders game, such as number recognition, step counting, and understanding the concept of sequence, can support the development of children's basic maths skills. The results proved that the Snakes and Ladders game not only teaches numbers and sequences but also develops cognitive skills such as planning and problem-solving, enhancing the intellectual development of children. In addition, the social interactions during the game enrich children's learning experience, improve communication skills, and strengthen the understanding of numerical concepts. The results suggest that the Snakes and Ladders game can improve children's numeracy skills and that the game can also be powerfully incorporated into the early childhood education curriculum as a tool that makes maths more fun and interactive.